Unraveling the mechanism of ethyl acetate extract from Prismatomeris connata Y. Z. Ruan root in treating pulmonary fibrosis: insights from bioinformatics, network pharmacology, and experimental validation - Li, Sizheng; Hu, Guang; Kuang, Lian; Zhou, Tianyu; Jiang, Haiyan; Pang, Fei; Li, Jie; Chen, Xinyi; Bao, Jie; Li, Wanfang; Li, Chuangjun; Li, Menglin; et al. (Frontiers in Immunology, 2024)
Pulmonary fibrosis (PF) is a terminal lung disease characterized by fibroblast proliferation, accumulation of extracellular matrix accumulation, inflammatory damage, and tissue structure destruction. The pathogenesis of this disease, especiallyparticularly idiopathic pulmonary fibrosis (IPF), is still remains unknown. Macrophages play a significant rolemajor roles in organ fibrosis diseases, including pulmonary fibrosis. The phenotype and polarization of macrophages are closely associated with the process of pulmonary fibrosis. A new direction in drug research on for antipulmonary fibrosis is focuseds on developing drugs that maintain the stability of the pulmonary microenvironment. Here, tThrough bioinformatics analysis and experiments involving bleomycin-induced pulmonary fibrosis in mice, we confirmed the importance of macrophage polarization in IPF. The analysis revealed that macrophage polarization in IPF involves a change in the phenotypice spectrum. Furthermore, the experiments demonstrated showed high expression of M2-type macrophage-related-associated biomarkers and inducible nitric oxide synthase, thus indicating an imbalance in M1/M2 polarization of pulmonary macrophages in mice with pulmonary fibrosis. Our investigation revealed that the ethyl acetate extract (HG2) obtained from the roots of Prismatomeris connataPrismatomeris connata Y. Z. Ruan exhibits therapeutic efficacy against bleomycin-induced pulmonary fibrosis. HG2 demonstrates the ability to modulates macrophage polarization, alterations in the TGF-β/Smads pSmad pathway, and downstream protein expression in the context of pulmonary fibrosis. Drawing upon On the basis of our findings, we believe that HG2 exhibits has potential as a novel component of traditional Chinese medicine component for treating pulmonary fibrosis.* p < 0.05; ** p< 0.01; *** p < 0.001.